Exploring the Implication of ChatGPT AI for Business: Efficiency and Challenges - Md Arman; Umama Rashid Lamiya (Journal of Innovation Information Technology and Application (JINITA), 2023)
This empirical study aims to examine the impact of ChatGPT AI on various business sectors, evaluating its benefits and challenges. Specifically, the study analyzes how ChatGPT AI is transforming business operations and enhancing customer experience in customer service, e-commerce, healthcare, finance, marketing, and developer business sectors. Using a comprehensive literature review approach, this study draws on relevant academic articles to identify and analyze the key applications of AI in the business sector, the benefits realized, and the challenges faced in adopting this technology. The study explores the implications of ChatGPT AI for businesses, including its potential to improve efficiency, reduce costs, and enhance competitiveness. Additionally, ethical and legal considerations surrounding the use of ChatGPT AI in business operations are evaluated, including issues related to data privacy, bias, and transparency. The study provides insights into future directions for the application of ChatGPT AI in business and the potential impact of this technology on various business sectors. The objective is to provide a comprehensive review of the impact of ChatGPT AI on businesses, its potential benefits, and challenges for businesses looking to adopt this technology. Overall, this study highlights the importance of considering both the benefits and limitations of AI adoption in businesses, as well as the ethical and legal implications of its use.